Development and Application of Seed Coating Agent for the Control of Major Soil-Borne Diseases Infecting Wheat - Xue-Xiang Ren; Chao Chen; Zheng-He Ye; Xian-Yan Su; Jin-Jing Xiao; Min Liao; Hai-Qun Cao (Agronomy, 2019)
In order to reduce the usage amount of pesticide fertilizers and protect the natural environment, seed coating agents are receiving increased wide concern. In this study, the active constituent (pesticide) and inactive components (surfactants and film former) of the seed coating agents were screened and optimized by the wet sand processing superfine grinding method. The fungal inhibition test of pesticides showed that thifluzamide, fludioxonil, pyraclostrobin, and difenoconazole have an obvious fungal inhibitory effect on wheat sharp eyespot, take-all, and root rot. LAE-9 and polyacrylamide + carboxymethyl cellulose (CMC) is recommended for the safe surfactant and film former, respectively, based on the seed germination test. Moreover, 6% difenoconazole · fludioxonil flowable concentrate for seed coating (FSC) stimulates the seedling growth of wheat, advances the growth of root, and improves biomass in the field trial, meanwhile, the control efficiency reached above 80%. Thus, we suggested it can be used as an effective seed coating agent for the control of soil-borne diseases in wheat. The seed coating agent has the characteristics of disease prevention, increasing crop yield, and safety of environment, which is of significance in practical application.